What are parents’ experiences of caring for their children with epilepsy? A qualitative systematic review and thematic synthesis, and; Mothers’ experiences of being told about the risk of sudden unexpected death in epilepsy (SUDEP) for their child: an interpretative phenomenological analysis - Galliard, Helen (The University of Edinburgh, 2018)
Systematic Review Abstract Background: Parents of children with epilepsy have been shown to have higher rates of depression, anxiety and stress in comparison to parents of children without epilepsy due to the impact of caring for a child with a chronic condition. A systematic review of existing literature aimed to identify qualitative research that examined parents’ experiences of caring for their children with epilepsy. Methods: The systematic review explored the experiences that parents have in caring for their child with epilepsy. A search of electronic databases for qualitative literature was completed. The quality of all eligible articles papers was assessed, and findings from studies were synthesised. Results: Twelve studies met inclusion criteria for the review; findings suggest that parents need time to process their child’s diagnosis of epilepsy; they cope with this in differing ways and are motivated to learn how to adapt and cope with parenting their child with epilepsy. Conclusions: Parents of children with epilepsy may experience symptoms of stress, this may motivate them to learn how best to care for their child. Empirical Paper Abstract Background: Parents’ experiences of being told about sudden unexpected death in epilepsy (SUDEP) may be particularly challenging to cope with. As little is known about how mothers understand and make sense of SUDEP, a qualitative research project aimed to explore mothers’ experiences. It was hoped this would be helpful for clinicians to understand in order to assist them in providing information to parents in a way that minimises distress. Methods: The empirical article explored mother’s experiences of being told about SUDEP and the subsequent impact of this for 11 mothers of children with epilepsy. Interpretative Phenomenological Analysis methodology was utilised, with themes derived from interpretation of interview transcripts, in order to describe the experiences of the participants. Results: Within the empirical study, five themes emerged. The way in which mothers found out about SUDEP seemed to have a link to their perception of risk and how they subsequently managed feelings of uncertainty and the psychological impact of knowing about SUDEP. Mothers’ recommendations to clinicians included when, how and what to tell other parents, and were based on their own helpful and unhelpful experiences of being informed about SUDEP. Conclusions: In being told about SUDEP, mothers may struggle to make sense of it and this can be associated with an increase in anxiety. However, clinicians can reduce potential distress by carefully timing when and how they tell parents, and by making sure information is clear and relevant for the child in question.
Mothers’ experiences of being told about the risk of sudden unexpected death in epilepsy (SUDEP) for their child: an interpretative phenomenological analysis.
Keywords: systematic review; epilepsy; parental experiences; sudden unexpected death in epilepsy; SUDEP; stress